2023
DOI: 10.1108/ara-10-2022-0266
|View full text |Cite
|
Sign up to set email alerts
|

Firm's value and ESG: the moderating role of ownership concentration and corporate disclosures

Abstract: PurposeThe study intends to determine the environment, social and governance (ESG)'s impact on the firm's value. In addition, how ownership concentration (OC) and transparency and disclosures (TD) influence the impact of firm's ESG on its valuation (firm value).Design/methodology/approachThe relevant panel data with a sample of 78 Indian firms for five years (2016–2020) are gathered. Both linear and nonlinear connections of firm's ESG with its value are tested. In addition, TD and two components of OC (stakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…On the contrary, it may benefit the personal interests of managers [76,94]. Additionally, Rastogi et al [95] propose that the outcomes of disclosure, transparency, and ownership are greatly influenced by agency theory. Therefore, the interest in utilizing these theories may stem from the lack of agreement in the literature concerning the connection between engaging in ESG activities and their influence on the firm's value.…”
Section: Theorymentioning
confidence: 99%
“…On the contrary, it may benefit the personal interests of managers [76,94]. Additionally, Rastogi et al [95] propose that the outcomes of disclosure, transparency, and ownership are greatly influenced by agency theory. Therefore, the interest in utilizing these theories may stem from the lack of agreement in the literature concerning the connection between engaging in ESG activities and their influence on the firm's value.…”
Section: Theorymentioning
confidence: 99%
“…Simultaneously, they suggested that financial performance (measured by RoE) and operating efficiency (measured by asset turnover) mediate this relationship. Rastogi et al (2023) in their recent work on ESG and firm value have concluded the nonlinear positive effect of ESG performance on the market value of the firm. Another research from Abdi et al (2022) has supported the positive effect of ESG disclosure on firm value as well as financial performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Although there have been many studies on the impact of ESG performance on corporate value at home and abroad, the research conclusions are different, and overall they can be divided into three types: First, researchers believe that ESG and corporate value are positively correlated, and ESG will promote the increase of corporate value [1][2][3][4]. With a change of research variables, ESG has a positive nonlinear (U-shaped) impact on enterprise value [5]. ESG can improve enterprise value by enhancing investor confidence [6].…”
Section: Introductionmentioning
confidence: 99%